Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Protects Striatal Cells and Improves Motor Function in Huntington's Disease Models: Role of PAC1 Receptor - Irene Solés-Tarrés; Núria Cabezas-Llobet; Benjamin Lefranc; Benjamin Lefranc; Jérôme Leprince; Jérôme Leprince; Jordi Alberch; Jordi Alberch; Jordi Alberch; David Vaudry; David Vaudry; Xavier Xifró (Frontiers Media S.A., 2022)
Huntington's disease (HD) is a hereditary neurodegenerative disorder caused by the expression of mutant huntingtin (mHtt). One of the main features of HD is the degeneration of the striatum that leads to motor discoordination. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide that acts through three receptors named PAC1R, VPAC1R, and VPAC2R. In the present study, we first investigated the effect of PACAP on STHdhQ7/Q7 and STHdhQ111/Q111 cells that express wild-type Htt with 7 and mHtt with 111 glutamines, respectively. Then we explored the capacity of PACAP to rescue motor symptoms in the R6/1, a murine model of HD. We found that PACAP treatment (10-7 M) for 24 h protects STHdhQ111/Q111 cells from mHtt-induced apoptosis. This effect is associated with an increase in PAC1R transcription, phosphorylation of ERK and Akt, and an increase of intracellular c-fos, egr1, CBP, and BDNF protein content. Moreover, the use of pharmacological inhibitors revealed that activation of ERK and Akt mediates these antiapoptotic and neurotrophic effects of PACAP. To find out PAC1R implication, we treated STHdh cells with vasoactive intestinal peptide (VIP), which exhibits equal affinity for VPAC1R and VPAC2R, but lower affinity for PAC1R, in contrast to PACAP which has same affinity for the three receptors. VIP reduced cleaved caspase-3 protein level, without promoting the expression of c-fos, egr1, CBP, and the neurotrophin BDNF. We next measured the protein level of PACAP receptors in the striatum and cortex of R6/1 mice. We observed a specific reduction of PAC1R at the onset of motor symptoms. Importantly, the intranasal administration of PACAP to R6/1 animals restored the motor function and increased the striatal levels of PAC1R, CBP, and BDNF. In conclusion, PACAP exerts antiapoptotic and neurotrophic effects in striatal neurons mainly through PAC1R. This effect in HD striatum allows the recovery of motor function and point out PAC1R as a therapeutic target for treatment of HD.